A Suppressed Primordial Priestly Lineage and Its Liturgical Revival - Noam, Vered (The Jewish quarterly review, 2026)
The rabbis banished from their own literature features of the works, literary style, and ideology typical of Second Temple Jewish culture. One example is the midrashic downgrading and denouncing of certain biblical figures regarded in the Second Temple period as part of a primordial priestly dynasty, as representatives of sectarian-priestly values. These same figures, however, are unexpectedly granted legitimacy and showcased in the High Holiday prayers, which serve as a treasure trove for ancient Jewish genres, ideas, and expressions that preceded, and countered, rabbinic values and beliefs. This essay examines and attempts to explain how these rejected biblical figures were surprisingly returned to their pristine glory in this unique, restricted corner.